The Impact of Training on Labour Mobility - Alan Felstead; Francis Green; Ken Mayhew; Alan Pack (University of Kent, Department of Economics, 1999)
The paper investigates the impact of different types of training on the mobility expectations of workers, using two new data sets, one of individuals the other of firms. The innovation is that the data incorporate measures of the degree of transferability of training, improved information on the sources of sponsorship, and judgements about the aims and outcomes of training. We find that most training episodes produce some transferable skills and that most transferable training is paid for by employers. Overall, training appears to have little impact on mobility. It has no impact on mobility in 3 out every 5 cases; the remaining cases are split equally between those where training increases and those where it decreases mobility. We estimate the determinants of mobility outcomes using an ordered probit analysis. Consistent with theory, we find that training is more likely to lead to lower mobility when it is less transferable to other firms, sponsored by firms, and where it has objectives and outcomes aimed at increasing the identification of employees with corporate objectives.
Keywords: J6; J24; 330; training; labour mobility; Berufsbildung; Arbeitsmobilität; Großbritannien; Makroökonomischer Einfluss